2019
DOI: 10.29173/cmplct29340
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Learning Progression of Complex Systems Understanding

Abstract: Recent research on what students know about complex systems shows that they typically have challenges in understanding particular system ideas such as nonlinearity, complex causality, and decentralized control. Yet this research has yet to adopt a systematic approach to learning about complex systems in an ordered way in line with the Next Generation Science Standards’ call for learning pathways that guide teaching and learning along a developmental continuum. In this paper, we propose that learning progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Few research studies have documented the learning trajectories that students take to understanding ecosystems. Our focus on learning trajectories is consistent with the recent emphasis on learning progressions (Duncan & Hmelo‐Silver, 2009; Duncan & Rivet, 2013; Duschl et al, 2007; Yoon et al, 2019). Taken together, there is a need to develop more precise mappings of learning trajectories and at smaller grain sizes.…”
Section: Tracing Systems Thinking Throughout An Interventionsupporting
confidence: 80%
See 2 more Smart Citations
“…Few research studies have documented the learning trajectories that students take to understanding ecosystems. Our focus on learning trajectories is consistent with the recent emphasis on learning progressions (Duncan & Hmelo‐Silver, 2009; Duncan & Rivet, 2013; Duschl et al, 2007; Yoon et al, 2019). Taken together, there is a need to develop more precise mappings of learning trajectories and at smaller grain sizes.…”
Section: Tracing Systems Thinking Throughout An Interventionsupporting
confidence: 80%
“…Although these explanatory accounts of systems may not necessarily fit canonical scientific explanations (Machamer et al, 2000), these show the necessity of connecting the visible SBF with the unseen, which Yoon et al (2019) found to be the most challenging facets of complex systems understanding for students to grasp. Yoon et al also suggest that the more visible facets—identifying different components, levels of the system, and how they interact—would be the most productive topics in middle school instruction, aligning with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the system can record individual behaviors while interacting with the system as much as possible. These data sources can offer the possibility of capturing evidence for identifying a meaningful problem-solving process and learning patterns [36,37]. This analytic framework is based on computational psychometrics.…”
Section: Discussionmentioning
confidence: 99%
“…Complexity concepts are entering some curricula, yet there are no discoverable approaches to the explicit teaching and learning of complexity thinking and understanding for students and educators in the Australian or US curriculums. For example, Yoon, Goh and Yang (2019) explain that while the Next Generation Science Standards (NGSS, 2013; National Research Council, 2012) incorporate complexity concepts into the framework for the American Science curriculum, their investigation into the development of explicit learning pathways for complexity thinking discovered that many students continue to attempt complexity understanding using linear cause and effect logic.…”
Section: Introductionmentioning
confidence: 99%